A generalized and comprehensive slant channel modeling method for underwater wireless optical communication and its system performance analysis - Ji, Xiuyang; Yin, Hongxi; Xing, Fangyuan; Jing, Lianyou; Shen, Zhongwei; Wang, Jianying; Liang, Yanjun (Optics communications, 2024)
The underwater wireless slant optical link is a more generalized type of communication links compared with vertical and horizontal links. Since several oceanic factors including temperature and salinity variations with the seawater depth, the performance of the slant link for the underwater wireless optical communication (UWOC) will be overestimated under the assumptions of constant temperature and salinity. To this end, this paper proposes a model of slant link considering the depth-dependent and inclination-angle-dependent turbulence and scattering that are the main causes of multipath fading for UWOC. Specifically, to model the turbulence-induced fluctuations of light fields, the random phase screen method is exploited, where the power spectrum of refractive index is calculated using the oceanic turbulence optical power spectrum (OTOPS) model and the light fields at the receivers are derived by the angular spectrum method. To emulate the scattering-induced divergence, the scattering phase function is applied, where the motion directions and coordinates of light spots propagating among phase screens are deduced using Rodrigues’ Rotation Formula. Simulation results demonstrate the effects of the depths and inclination angles of transmitters on the performance of UWOC by analyzing the scintillation index, channel impulse response, and BER (bit error rate). •Considering the distinctions of seawater parameters for different depths, we establish an underwater wireless optical slant link model, where the aggregated impairments caused by absorption, scattering, and turbulence are reconstructed by utilizing the multiple phase screens to stratify the seawater in the vertical direction.